2022
DOI: 10.3389/fcvm.2022.856796
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Left Atrial Fibrosis and Success of Catheter Ablation by Speckle Tracking Echocardiography in Patients Imaged in Persistent Atrial Fibrillation

Abstract: BackgroundNon-invasive evaluation of left atrial structural and functional remodeling should be considered in all patients with persistent atrial fibrillation (AF) to optimal management. Speckle tracking echocardiography (STE) has been shown to predict AF recurrence after catheter ablation; however in most studies, patients had paroxysmal AF, and STE was performed while patients were in sinus rhythm.AimThe aim of this study was to evaluate the ability of STE parameters acquired during persistent AF to assess a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…In the present study, we noticed a significantly increased PA‐TDI duration after the completion of chemotherapy, suggesting the atrial electrical and structural remodeling induced by anthracycline toxicity. The LASr has been reported to be associated with the extent of low‐voltage area in patients with AF 38 . Quantitative analysis further validated a solid inverse correlation between LASr and LA fibrosis confirmed with histopathology 39 and enhanced cardiac magnetic resonance (CMR) 40,41 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the present study, we noticed a significantly increased PA‐TDI duration after the completion of chemotherapy, suggesting the atrial electrical and structural remodeling induced by anthracycline toxicity. The LASr has been reported to be associated with the extent of low‐voltage area in patients with AF 38 . Quantitative analysis further validated a solid inverse correlation between LASr and LA fibrosis confirmed with histopathology 39 and enhanced cardiac magnetic resonance (CMR) 40,41 .…”
Section: Discussionmentioning
confidence: 68%
“…The LASr has been reported to be associated with the extent of low-voltage area in patients with AF. 38 Quantitative analysis further validated a solid inverse correlation between LASr and LA fibrosis confirmed with histopathology 39 and enhanced cardiac magnetic resonance (CMR). 40,41 Therefore, LASr not only reflects LA function status but also the degree of pathological remodeling.…”
Section: Lasr Is a Promising Index For The Early Diagnosis Of Anthrac...mentioning
confidence: 78%
“…and all measurements were performed by averaging 3 cardiac cycles as described previously. 13 LV volumes and ejection fraction were calculated using Simpson’s biplane method. The E/e′ ratio was calculated from peak mitral flow E and the average of septal and lateral e′ tissue Doppler velocities.…”
Section: Methodsmentioning
confidence: 99%
“…Electroanatomic mapping of the LA was obtained using the ConfiDENSE CARTO3 system v6.0.70 using the 2515 Variable Loop Lasso Multi-Electrode Eco Nav (Biosense Webster) using ≥1,000 measurements as described previously. 13 Electrical cardioversion was attempted after an initial mapping, and mapping was repeated in SR. Low voltage area was defined as bipolar peak-to-peak voltage amplitude of <0.5 mV in SR and <0.31 mV in AF. All patients underwent radiofrequency PVI with additional lines or complex atrial fractionated electrogram ablations performed at the physician's discretion.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally acknowledged that atrial structural remodeling involving atrial tissue fibrosis and scarring is an essential factor in the pathogenesis and progression of AF ( 7 , 8 ). Several trials have suggested that the existence of LVA was strongly associated with AF recurrence after catheter ablation for all AF types ( 9 12 ). In this context, in Rolf et al initially proposed LVA-guided ablation as an atrial substrate modification approach ( 9 ).…”
Section: Introductionmentioning
confidence: 99%